Transinfection of bed bug (Cimex hemipterus) wolbachia into dengue vector mosquito (Aedes aegypti) by microinjection - Srettapong Thimaharn (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2007